Ultrasound Technologies for Food and Bioprocessing - Feng, Hao; Barbosa-Canovas, Gustavo; Weiss, Jochen (Food Engineering Series, 2011)
Traditional food and bioprocessing technologies are facing challenges due to high expectations from consumers and producers in their demand for better quality and safety, higher process efficiencies, and products with novel properties or functionalities. For these reasons, in the last few years new forms of physical energy have been explored as alternatives to traditional processing technologies. Acoustic energy has the potential to replace or partially substitute for conventional processes; and at the same time, it could offer unique opportunities in the characterization of foods and biomaterials. This book is a resource for experts and newcomers in the field of power ultrasound, giving insights into the physical principles of this technology, detailing the latest advancements, and linking them to current and potential applications in the food and bioprocessing-related industries.